IMPLEMENTASI SIFAT-SIFAT RASULULLAH DALAM JURNALISTIK PADA REDAKSI TRIBUN JABAR - Diansah, Rano Hardiana (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2017)
The research method used is a qualitative method with a case study approach. By conducting observations and in-depth interviews with research with a qualitative approach use phenomenological methods and interpretative paradigms. This paradigm sees that the truth of social reality is a different result depending on the social actors. Through the constructivism paradigm, the researcher wants to know how the subject captures a prophetic journalism phenomenon in his daily life so that it can be subjects according to their understanding of each application. This research confirms that Tribun Jabar has implamented prophetic journalism in producing news, although not comprehensively, but at least journalist at Tribun Jabar have implamented the 4 morals of the prophets and apostles in journalistic activities in the field.